The case against Christ - Young, John, 1937-; Wilkinson, David (London, UK, Hodder and Stoughton, 2006)
Contents : Questions : mainly about the church and society - Questions about science and faith - Questions about the Bible - Questions about suffering - Questions about Jesus - Prove it! Does God exist.
Keywords: Jesus Christ -- Divinity; Jesus Christ -- Historicity; Apologetics